Sensitivity of Computed Tomography for the Assessment of Spontaneous Dermoid Cyst Localized Rupture with Granulomatous Reaction - Galindo-Ferreiro, Alicia; Elkhamary, Sahar M; Aldossari, Saif; Akaishi, Patricia M.; Alkatan, Hind; Khandekar, Rajiv; Garcia, Denny Marcos; Muiños-Diaz, Yerena; Schellini, Silvana A [UNESP]; Cruz, A. Augusto V. (Taylor & Francis, 2018)
Purpose: To assess the sensitivity of computed tomography for the diagnosis of spontaneous localized orbital dermoid cyst rupture with granulomatous reaction. Methods: The charts of 42 patients with dermoid cysts were reviewed retrospectively. The data collected included demographics, clinical features, CT imaging, and postoperative histopathological analysis of the lesions. The association between radiological signs of inflammation and histopathological evidence of an inflammatory reaction was tested by univariate logistic regression. Results: Localized spontaneous rupture with granulomatous reaction occurred in 61.9% of patients. The median age of patients with spontaneous rupture was significantly higher than the age of patients who had no histopathological evidence of rupture. Bone scalloping was significantly associated with preoperative rupture. Fat contents had a protective effect. Large sizes increased the odds of rupture. Conclusion: Bone remodeling and histopathological evidence of spontaneous preoperative rupture were significantly associated. Since age, cyst size, and contents are factors contributing to rupture, surgical removal is suggested for dermoids with liquid contents.
Keywords: Dermoids; histology; imaging; orbit; surgery